2016
DOI: 10.3171/2014.12.jns142110
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of ankle movements with the ActiGait implantable drop foot stimulator: a safe and reliable treatment option for permanent central leg palsy

Abstract: OBJECT The ActiGait drop foot stimulator is a promising technique for restoration of lost ankle function by an implantable hybrid stimulation system. It allows ankle dorsiflexion by active peroneal nerve stimulation during the swing phase of gait. In this paper the authors report the outcome of the first prospective study on a large number of patients with stroke-related drop foot. METHODS Twenty-seven patients who experienced a stroke and with persisting spastic leg paresis received an implantable ActiGait dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
3
10
0
1
Order By: Relevance
“…The aim of this study was to elucidate whether the Ac-tiGait implantable drop foot stimulator can provide longterm improvements in gait speed and endurance and re- duce the risk of falls in patients with MS-related drop foot, because its efficacy and superiority over surface stimulation in patients after stroke were reported recently. 10,16 In this study, no adverse events were observed. Until now, only rare complications, such as hematoma and lymphedema (both in 1 of 5 patients), 16 wound-healing deficit (1 of 15 patients) and infections (2 of 15 patients), 3 and injury to the peroneal nerve (2 of 27 patients), 10 have been reported.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The aim of this study was to elucidate whether the Ac-tiGait implantable drop foot stimulator can provide longterm improvements in gait speed and endurance and re- duce the risk of falls in patients with MS-related drop foot, because its efficacy and superiority over surface stimulation in patients after stroke were reported recently. 10,16 In this study, no adverse events were observed. Until now, only rare complications, such as hematoma and lymphedema (both in 1 of 5 patients), 16 wound-healing deficit (1 of 15 patients) and infections (2 of 15 patients), 3 and injury to the peroneal nerve (2 of 27 patients), 10 have been reported.…”
Section: Discussionmentioning
confidence: 50%
“…10,16 In this study, no adverse events were observed. Until now, only rare complications, such as hematoma and lymphedema (both in 1 of 5 patients), 16 wound-healing deficit (1 of 15 patients) and infections (2 of 15 patients), 3 and injury to the peroneal nerve (2 of 27 patients), 10 have been reported. The surgery and postoperative care were easy and uncomplicated.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…During the past decade a few studies have investigated the effects of implanted systems on gait [2732] and quality of life [26, 30, 32]. Most of them found an increase in walking speed and dorsal extension of the ankle during swing phase and/or initial contact as well as good patient-reported device satisfaction and improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…So wird z. B. in der vergleichbaren Studie mit einem implantierbaren Stimulator von Martin et al eine deutliche Verbesserung der Ganggeschwindigkeit von 47,2 % beschrieben[10]. Ebenso beschreiben Studien, die das Outcome von ex-…”
unclassified